Three-dimensional printed PCL-hydroxyapatite scaffolds filled with CNTs for bone cell growth stimulation - Goncalves, Elsa M.
A three-phase [nanocrystalline hydroxyapatite (HA), carbon nanotubes (CNT), mixed in a polymeric matrix of polycaprolactone (PCL)] composite scaffold produced by 3D printing is presented. The CNT content varied between 0 and 10 wt % in a 50 wt % PCL matrix, with HA being the balance. With the combination of three well-known materials, these scaffolds aimed at bringing together the properties of all into a unique material to be used in tissue engineering as support for cell growth. The 3D printing technique allows producing composite scaffolds having an interconnected network of square pores in the range of 450-700 m. The 2 wt % CNT scaffold offers the best combination of mechanical behaviour and electrical conductivity. Its compressive strength of approximate to 4 MPa is compatible with the trabecular bone. The composites show typical hydroxyapatite bioactivity, good cell adhesion and spreading at the scaffolds surface, this combination of properties indicating that the produced 3D, three-phase, scaffolds are promising materials in the field of bone regenerative medicine. (c) 2015 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 104B: 1210-1219, 2016.